Work programme 2013 - (:unkn) unknown (Publications Office of the European Union, 2013)
Cedefop's 2013 work programme is consistent with its medium-term priorities 2012-14. Chapter 2 outlines the policy background, taking account of the overall strategy set by 'Europe 2020' and further recent policy developments, e.g. the Commission communications 'Youth employment' and 'Rethinking education' and the related staff working paper 'VET for better skills, growth and jobs'. Chapters 3 to 5 give an overview of the planned activities by medium-term priority. Chapters 6 and 7 present communication activities as well as those planned for management and administration of Cedefop for 2013. (BIBB-Doku)
Keywords: S 3.5.5.1 CEDEFOP; S 2.3 Berufsbildungspolitik; CEDEFOP; Programm; Berufsbildung; Förderung; Internationale Zusammenarbeit; Berufsbildungspolitik; Europäische Union